ANALYSIS OF CONSTRUCTION MANAGEMENT MAIN ROAD IN THE CISUMDAWU STA.21+200 – STA.22+825 TOLL ROAD PROJECT - Prasetio, Iko; Anwar, Saihul (Journal of Green Science and Technology, 2020)
Construction management is an attempt to use limited resources efficiently, effectively and timly in completing a project that has been palnned. There are 3 kinds of basic functions of construction management including planning, implementation, and control. Of three of these activities to control the resources on aproject that includes worker, equipment, material, money, and method.The research method used was qualitative research, as a way of collecting data on the study is how the study of the literature, interviews and direct observation in field. And this method is a method that is done to get a foundation theory in analyzing data, namely the analysis calculation of the volume of material, analysis of labor, analysis tool, method, method of Bar Chart S Curve and Critical Path Method.The location of the studies reviewed were Main Road in the Cisumdawu STA.21+200 ? STA.22+825 Toll Road Project , located on Pamatutan Hamlet Mulyasari ? Pasir Hamlet Margamukti, Sumedang. The results of this research is the budget plan costs  completed the construction of Main Road in the Cisumdawu STA.21+200 ? STA.22+825 Toll Road Project till the final stage more or less cost is Rp. 121.488.578.000 and analysis of the Critical Path Method (CPM) estimated completion of the Main Road in the Cisumdawu STA.21+200 ? STA.22+825 Toll Road Project takes 58 weeks (406 days).Keywords: Construction Management, Bar Chart, S Curve, Critical Path Method.